Melatonin-induced oncostasis, mechanisms and clinical relevance - Cardinali, Daniel Pedro (2016)
Fil: Cardinali, Daniel P. Pontificia Universidad Católica Argentina. Facultad de Ciencias Médicas. Instituto de Investigaciones Biomédicas; Argentina